Influência da composição do substrato no desempenho térmico de telhados verdes - Schmidt, Matheus (2020)
In the last decades, green roofs have become a key element in urban composition in developed countries, especially due to the thermal comfort they promote to the building. In order to obtain a better thermal performance, the ideal substrate must be adapted to the climate in which it is installed, depending on its physical properties. The aim of this work is to evaluate the use of the green roof in buildings with a focus on energy efficiency and environmental thermal comfort, through the analysis of 7 prototypes, which configure the treatments. 3 of these are green roof prototypes with substrate and vegetation cover, 3 are green roof prototypes with substrate without vegetation cover, and one is a prototype with conventional roof of clay tiles (control). Three types of substrate were evaluated, a clay soil with a slight organic matter content (humus, 5%), a sandy substrate with a light organic matter content (humus, 5%), and a substrate entirely composed of organic matter (bovine manure and dry vegetable matter). The ambient temperature (internal and external), and the temperature of the substrates (response variables) were continuously monitored for a period of one month, using the digital capacitive sensor AM2302-DHT22 and the digital sensor DS18B20, respectively, connected to the Arduino Mega microprocessor. The best thermal performance was observed in the prototype of sandy substrate with vegetation, presenting, in the hottest times, an internal temperature at least 0.6 ° C lower than the other green roofs, 1.7 ° C lower than the control and 6.1 ° C below room temperature, presumably due to the high porosity of this substrate. It is concluded that for the substrate to provide ideal thermal performance, it must have water retention capacity just enough to guarantee vegetation development, but not excessive enough to constantly increase thermal conductivity due to substrate saturation.